Socio-cultural relations in the Polish-Lithuanian period of history of Ukraine (XIV-XVI centuries) - Маложон, Олена Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
In the article the social and cultural relations of Ukraine are analyzed in composition Lithuania and Poland in XIV – to the first half of the XVI item. The author concludes that this period is characterized by the formation of Ukrainian nationality, cultural revival, and the spread of Reformation ideas of humanism, social, national revolutions. From the middle of the XIII century Kievan Rus had undergone the devastating attacks of the Mongol-Tatar hordes that had disastrous consequences for its economy and culture. Then it was under the rule of Lithuania and Poland, which influenced the cultural and moral development of the Ruthenian (Ukrainian) people. Under these conditions a process of feudal fragmentation intensified and also processes of ethno genesis deepened. Ukrainian nation acted as a separate community with its own language, territory, economic life and native culture. The formation of Ukrainian nationality was accompanied by aggravation of social contradictions caused by the struggle of the masses against foreign oppression